MANAJEMEN PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH - Edi Marwan (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2017)
Quality in the context of integrated quality management or Total Quality Management (TQM) is not only an idea, but a philosophy and methodology in helping institutions to manage changes in totality and systematic, through changes in values, vision, mission and goals. Because in the world of quality education graduates of a school are assessed based on their ability to suit the goals set in the curriculum.